In search of sustainability: the evolution of sustainable business models through dynamic capabilities - Kumasaka, Júlia Mitsue Vieira Cruz (2025)
To meet the demands of their stakeholders and make an effective contribution to sustainable development, organisations need to make significant changes to their business models to make them more sustainable. Sustainable business models (SBM) have all its elements aimed at delivering value to different stakeholders, including the environment and society in general. However, making the necessary changes to adopt this type of business model is not simple. Thus, dynamic capabilities can play a crucial role in this process by enabling the organization to adapt internally in response to changes in the external environment. Thus, the aim of the present research is to analyse how traditional business models of companies evolve towards sustainable business models through the lens of dynamic capabilities. To this end, a multiple case study was conducted with large companies that implemented significant changes toward sustainability in their business models. Data collection took place in two ways. First, through documents such as companies sustainability reports, websites and social media, in addition to the internal documents that were provided. Seecond, with semi-structured interviews with managers who worked on actions related to the change from a traditional business model to an SBM. The contributions and implications of this study can be understood as follows: (1) Theoretical: they include a deeper exploration of the relationship between dynamic capabilities and business model innovation for sustainability, as well as a detailed account of this transformation process, which remains underexplored in the literature; (2) Practical: the findings can support managers in formulating strategies to gradually transform traditional business models into sustainable ones; (3) Social: by helping large companies understand how they can become more sustainable, this study contributes to enabling these organizations to positively influence the pursuit of sustainable development.